2008
DOI: 10.1159/000149782
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Cisplatin-resistance in Malignant Mesothelioma Cells Abrogates Na<sup>&plus;</sup>,K<sup>&plus;</sup>,2Cl<sup>-;</sup>-cotransport Activity and Cisplatin-induced Early Membrane Blebbing

Abstract: Aims: Resistance mechanisms are important limiting factors in the treatment of solid malignancies with cis-diamminedichloroplatinum(II) (cisplatin). To gain further understanding of the effects of acquired cisplatin-resistance, we compared a human malignant pleural mesothelioma cell line (P31) to a sub-line (P31res1.2) with acquired cisplatin-resistance. Methods and Results: The role of Na+,K+,2Cl--cotransport (NKCC1) activity in cisplatin-induced morphological changes and acqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 38 publications
3
24
0
Order By: Relevance
“…Janson and coworkers have demonstrated that cisplatin resistance in malignant mesothelioma cells involves a marked reduction in the Na + ,K + ,2Cl -cotransport (NKCC1) activity [39]. However, the reduced NKCC1 activity was not important for the cisplatin resistance [39]. In agreement we find that NKCC activity counteracts ion and water loss during apoptosis [18].…”
Section: Cisplatin Resistance In Adherent Vs Non-adherent Cancer Cellssupporting
confidence: 86%
See 1 more Smart Citation
“…Janson and coworkers have demonstrated that cisplatin resistance in malignant mesothelioma cells involves a marked reduction in the Na + ,K + ,2Cl -cotransport (NKCC1) activity [39]. However, the reduced NKCC1 activity was not important for the cisplatin resistance [39]. In agreement we find that NKCC activity counteracts ion and water loss during apoptosis [18].…”
Section: Cisplatin Resistance In Adherent Vs Non-adherent Cancer Cellssupporting
confidence: 86%
“…The reduced sensitivity to cisplatin in MDR EATC was correlated with a low activity of the volume-sensitive Cl -channel [18]. Janson and coworkers have demonstrated that cisplatin resistance in malignant mesothelioma cells involves a marked reduction in the Na + ,K + ,2Cl -cotransport (NKCC1) activity [39]. However, the reduced NKCC1 activity was not important for the cisplatin resistance [39].…”
Section: Cisplatin Resistance In Adherent Vs Non-adherent Cancer Cellsmentioning
confidence: 99%
“…The mesothelioma cell model P31 and its respective cisplatin-resistant subline P31/cis have been generously donated by K. Grankvist (Umeå University, Sweden). 48 The non-small-cell lung cancer cell model SW1573 with its MRP1-and LRP-overexpressing subline 2R120 and its P-gp-overexpressing subline 2R160 is from H. Broxterman (Department of Medical Oncology, Free University Hospital, Amsterdam, The Netherlands). 53 The ovarian carcinoma model A2780 with its cisplatin-selected subline A2780/cis was purchased from Sigma-Aldrich.…”
Section: Cell Lines and Culture Conditionsmentioning
confidence: 99%
“…12 The fluorescein diacetate cytotoxicity test performed in parallel with the detection of oligonucleosomal DNA fragmentation using, for example, terminal deoxynucleotidyl transferase-mediated dUT nick-end labelling assay can be used as an end-point assay for cellular apoptosis. 13 …”
mentioning
confidence: 99%
“…However, in a cell model of acquired cisplatin resistance in malignant pleural mesothelioma cells we have previously shown that P31res1.2 cells have reduced NKCC1 activity and disrupted K + -regulation. 13 It cannot be excluded that these changes may affect caspase activity, as well as, for example, accumulation and intra-cellular trapping of cisplatin. Furthermore, both caspase-3 and caspase-7 can cleave DNA fragmentation factor 45/inhibitor of caspase-activated DNase (DFF45/ICAD) and release active DNA fragmentation factor 40/caspase-activated DNase nuclease (DFF40/CAD), which forms homo-oligomers and generates double-strand breaks in DNA.…”
mentioning
confidence: 99%